Aspiration and Sclerotherapy with Sodium Tetradecyl Sulfate Versus open Hydrocelectomy: An Experience with the Two Modalities of Hydrocele Management - Memon, Muhammad Munir; Salati, Sajad Ahmad; Memon, Mashhood; Malik, Faiza Riaz; Saadia, Zaheera; Shehzad, Khalid (Lietuvos chirurgija, 2025)
Background. Hydrocele is the most prevalent cause of painless scrotal swelling. Hydrocelectomy is the gold standard of management for symptomatic hydrocele, but in recent years, aspiration and sclerotherapy have been tried as minimally invasive treatment modalities. Aim of the study. The study aims to evaluate the efficacy, safety, and cost-effectiveness of percutaneous aspiration and sclerotherapy with sodium tetradecyl sulfate (STS) compared to the standard open hydrocelectomy procedure for the treatment of symptomatic hydroceles. Methods. A retrospective analysis of the cases that were treated for symptomatic hydroceles between January 2019 and December 2023 with either open hydrocelectomy or percutaneous aspiration followed by sclerotherapy with a sodium tetradecyl sulfate-based solution was conducted. This study was undertaken after obtaining formal permission from the ethics committee. Primary outcomes included patient satisfaction and procedural success, while secondary outcomes focused on complications and the comparative costs of the procedures. Results. Thirty-seven patients were treated with aspiration and sclerotherapy, and these patients were compared with 34 patients who underwent hydrocelectomy. The mean follow-up for the aspiration and sclerotherapy group was 10.6 months, and for the hydrocelectomy group, it was 18.2 months. The patient satisfaction rate was 76% for aspiration and sclerotherapy and 90% for hydrocelectomy. The overall success rate for aspiration and sclerotherapy was 76%, compared to 86% for hydrocelectomy. The complication rate was significantly lower for aspiration and sclerotherapy (12%) compared to hydrocelectomy (29%). The cost of hydrocelectomy was almost twelve times higher than aspiration and sclerotherapy. Conclusions. Aspiration and sclerotherapy with sodium tetradecyl sulfate provide a minimally invasive, cost-effective, and safe alternative to open hydrocelectomy. Although the success rate is slightly lower than that of hydrocelectomy, its simplicity, lower complication rate, and significantly reduced cost render it a cost-effective and practical first-line approach for managing hydroceles in appropriately selected cases.